Complicaciones perinatales y vías de parto en recién nacidos de madres adolescentes en el hospital de contingencia Minsa II-2 Tarapoto durante el periodo julio noviembre 2015 - Tocto Llacsahuanga, Marisol (2016)
OBJECTIVES: Learn about the perinatal complications and birth pathways in newborns of early and late adolescent mothers. MATERIALS AND METHODS: A basic, observational, prospective, cross- sectional, descriptive study of 177 pregnant adolescents assisted at the Minsa II-2 Tarapoto Hospital during the period of July-November 2015, it has been evaluated the way of birth and perinatal complications. Adolescents were classified as early (10-14 years old) and late (15-19 years old). RESULTS: The 40.1% of births in the study period were from newborns of adolescent mothers. There was a total of 177 births in adolescents, 10.7% of them, belonging to early adolescence. Low birth weight was the most frequent perinatal complication with 15.3% of newborns, followed by prematurity with 13% and SDR with 11.3%, 9.6% had neonatal sepsis, 7.3% with hypoglycemia, and depression at birth was present in 6.2%. Cesarean delivery occurred in 52.5% of newborns, the main indication for cesarean section was pelvic stricture. CONCLUSION: The main perinatal complications in births in adolescent in the MINSA II-2 Tarapoto Hospital were, low birth weight, prematurity, RDS. The main pathways of delivery was cesarean